Clinical guidelines of the Russian gastroenterological association on diagnostics and treatment of chronic constipation in adults - V. T. Ivashkin; S. R. Abdulkhakov; Ye. K. Baranskaya; T. L. Lapina; I. V. Mayev; M. F. Osipenko; Ye. A. Poluektova; V. I. Simanenkov; A. S. Trukhmanov; A. A. Sheptulin; O. S. Shifrin; I. B. Khlynov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.